The birds of Siberut, Mentawai Islands, West Sumatra - Neville Kemp (Indonesian Ornithologists’ Union, 2000)
The island of Siberut is the largest of the Mentawai Archipelago, which lies 125145 km from the coast of mainland West Sumatra. Primary lowland rain forest and freshwater swamp forest cover is extensive on Siberut, and supports a unique fauna with high levels of endemism, the most studied examples of which are the four endemic species of primates. The Mentawais also have an endemic species of Scopsowl Otus mentawi as well as 12 other birds endemic at the subspecific level. Unlike the primates and other mammals however, the avifauna has been poorly studied and its ecology is not well understood. Information is provided on bird surveys carried out between August 1997 and March 2000 whilst the author lived and worked on the island for the Siberut National Park Authority. Data are presented for Siberut bird communities, including significant bird records during the 2½ year period. These records include 28 new species for the island, three new provincial records (Whiteheaded Stilt Himantopus leucocephalus. Gullbilled Tern Gelochelidon nilotica and Pomarine Jaeger Stercorarius pomarinus) and a new record for Sumatra (Grey-tailed Tattler Heteroscelus brevipes). A discussion about the threats to Siberut's forests and the future impact that these will have on the bird population of Siberut is given. An appendix lists all 134 species recorded on Siberut, with information on habitat, status and abundance.